Knowledge, Attitudes, and Agricultural Practices of Coconut Farmers on the Impacts of Climate Change on Coconut Productivity and Sustainability in Barangay Capasnan, Manay, Davao Oriental, Philippines - Bentayao, Chinna M.; Verzosa, Ricksterlie C.; Vilela, Eleanor M.; Nemenzo-Calica, Phoebe (Journal of Tropical Crop Science, 2025)
Coconut, a vital tropical crop, and the Philippines’ leading agricultural export, particularly in Davao Oriental, the “Coconut Capital” of the country, is profoundly impacted by climate change, which disrupts its productivity and agricultural practices, thereby threatening its sustainability. This study evaluated the knowledge, attitudes, practices, perceived impacts, and preparedness of coconut farmers in Barangay Capasnan, a major contributor to Davao Oriental’s coconut production. A descriptive research design was employed, with 145 farmers (out of 227 registered) participating through purposive sampling. Data were collected through validated surveys, analyzed with descriptive statistics, and conducted under ethical guidelines. Results showed that most farmers (30%) were over 61 years old, with 59% male and 41% female participants. A majority (63%) had only elementary-level education, and most households (56%) comprised 1-4 members. Nearly all farmers (94%) owned their farms, but 59% had a monthly income below PHP 10,000 (~USD 170.24). Farmers demonstrated a high awareness of climate change, recognizing its effects on temperature, rainfall, seasonality, and its role in exacerbating extreme weather, pests, and diseases. They perceived climate change as a significant threat to agriculture, advocating for education and action, though engagement in community coping strategies remained moderate. Farmers implemented practices such as knowledge-sharing, exploring alternative income sources, investing in protective infrastructure, and planning for renewable energy use. However, moderate adoption was observed in water-saving irrigation, drought-resistant crops, soil conservation, and pest management practices. Climate change was perceived to have severe impacts on coconut yields, quality, soil fertility, seasonal patterns, and labor demands, while moderate impacts included extreme weather, water scarcity, and heat stress. Recommendations include providing emotional and mental support, financial assistance, access to resilient crop varieties, climate-smart agricultural training, affordable adaptive technology, and increased distribution of coconut seedlings by the Philippine Coconut Authority to address declining quality and productivity caused by weather changes.